Above‐ and belowground linkages in Sphagnum peatland: climate warming affects plant‐microbial interactions. (15th December 2012) - Jassey, Vincent EJ; Chiapusio, Geneviève; Binet, Philippe; Buttler, Alexandre; Laggoun‐Défarge, Fatima; Delarue, Frédéric; Bernard, Nadine; Mitchell, Edward AD; Toussaint, Marie‐Laure; Francez, André‐Jean; Gilbert, Daniel
Abstract Peatlands contain approximately one third of all soil organic carbon (SOC). Warming can alter above‐ and belowground linkages that regulate soil organic carbon dynamics and C‐balance in peatlands. Here we examine the multiyear impact of in situ experimental warming on the microbial food web, vegetation, and their feedbacks with soil chemistry. We provide evidence of both positive and negative impacts of warming on specific microbial functional groups, leading to destabilization of the microbial food web. We observed a strong reduction (70%) in the biomass of top‐predators (testate amoebae) in warmed plots. Such a loss caused a shortening of microbial food chains, which in turn stimulated microbial activity, leading to slight increases in levels of nutrients and labile C in water. We further show that warming altered the regulatory role of Sphagnum‐polyphenols on microbial community structure with a potential inhibition of top predators. In addition, warming caused a decrease in Sphagnum cover and an increase in vascular plant cover. Using structural equation modelling, we show that changes in the microbial food web affected the relationships between plants, soil water chemistry, and microbial communities. These results suggest that warming will destabilize C and nutrient recycling of peatlands via changes in above‐ and belowground linkages, and therefore, the microbial food web associated with mosses will feedback positively to global warming by destabilizing the carbon cycle. This study confirms that microbial food webs thus constitute a key element in the functioning of peatland ecosystems. Their study can help understand how mosses, as ecosystem engineers, tightly regulate biogeochemical cycling and climate feedback in peatlands